Anterior uveitis as a manifestation of ocular tuberculosis - Câmara,Stephanie do Nascimento (2019)
ABSTRACT Tuberculosis (TB) is an infectious disease of great magnitude in the world. Of patients with extrapulmonary disease, ocular manifestations are rare but among reported cases the most common ocular manifestation is uveitis. The diagnosis of ocular TB should be made as early as possible so that treatment is initiated and the risks of ocular complications are minimized. The objective of this study is to report an ocular TB case that presented as anterior uveitis. A 52-year-old female patient, a nursing technician at a large hospital, presented a history of low visual acuity associated with myiodesopsia for 4 days. Her ophthalmologic history included an iridotomy due to narrow angle in both eyes. On examination, the best corrected visual acuity was 20/100, right eye, and 20/80, left eye. Among the most significant ocular alterations were granulomatous keratic precipitates, anterior chamber reaction, flare and light vitreitis, corresponding to anterior uveitis. Based on clinical history and ophthalmologic examination, tests were ordered that corroborated the diagnosis of ocular TB. Thereafter, antituberculous therapy was instituted with a good response in 15 days, including improvement in visual acuity. The patient was followed-up by ophthalmology and infectology. Intraocular TB should be considered in the differential diagnosis of any type of intraocular inflammation. The diagnosis of presumed ocular TB is a clinical challenge with the diagnosis modalities currently available. The faster the onset of treatment, the better the visual prognosis of the affected patient.